Analisis Terhadap Putusan Hakim Dalam Kasus Cerai Gugat : (Studi Putusan Nomor 64 / Pdt.G./2013/PA.Mtr) - Riza Anissa Triana; Sahruddin Sahruddin (Private Law, 2023)
This research aims are to know judge’s consideration in decided divorce case in Verdict Number 64/Pdt.G./2013/PA.Mtr and to know legal consideration in the verdict. Type of this study was normative research, which applied statute, conceptual and case approach. The causing factor of divorce as stated in the verdict were economic issues which triggered dispute continuously between husband and wife, and eventually harmony between husband and wife did not able to be restored anymore. Judge’s consideration in the case based on judge assembly had tried in order to defendant and plaintiff can live together in harmony, and judge’s consideration in Mataram Islamic Court which grant the plaintiff’s claim and charge her to pay the court fees.